2020
DOI: 10.1371/journal.pone.0221008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation for root architectural traits in response to phosphorus deficiency in mungbean at the seedling stage

Abstract: Roots enable the plant to survive in the natural environment by providing anchorage and acquisition of water and nutrients. In this study, root architectural traits of 153 mungbean genotypes were compared under optimum and low phosphorus (P) conditions. Significant variations and medium to high heritability were observed for the root traits. Total root length was positively and significantly correlated with total root surface area, total root volume, total root tips and root forks under both optimum P

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 82 publications
7
26
0
Order By: Relevance
“…Increased root growth is associated with improved ability of plants to mine soil moisture and nutrients. Our findings are in conformity with studies in lentil [57], green gram [58,59], soybean [60], and wheat [61] indicating low P alters root architectural traits such as total root length, surface area, and root-to-shoot ratio. Increased root-to-shoot ratio is associated with higher investment of photosynthates towards root growth, which further enhances P acquisition.…”
Section: Interaction Of Low P and Drought On Growth And Root Traits Isupporting
confidence: 92%
“…Increased root growth is associated with improved ability of plants to mine soil moisture and nutrients. Our findings are in conformity with studies in lentil [57], green gram [58,59], soybean [60], and wheat [61] indicating low P alters root architectural traits such as total root length, surface area, and root-to-shoot ratio. Increased root-to-shoot ratio is associated with higher investment of photosynthates towards root growth, which further enhances P acquisition.…”
Section: Interaction Of Low P and Drought On Growth And Root Traits Isupporting
confidence: 92%
“…Increased root growth is associated with improved ability of plants to mine soil moisture and nutrients. Our findings are in conformity with studies in lentil [57], green gram [58,59], soybean [60] and wheat [61] indicating low P alters root architectural traits such as total root length, surface area and root-to-shoot ratio. Increased root-to-shoot ratio is associated with higher investment of photosynthates towards root growth which further enhances P acquisition.…”
Section: Interaction Of Low P and Drought On Growth And Root Traits Isupporting
confidence: 92%
“…In contrast, the root depths of wild species (G1, G2, and G3) were not significantly affected by low P. Whether or not this reveals a trend for wild species in natural soils to adapt to a large range of P availability requires further investigation. In a large collection of mungbean genotypes (153 genotypes), Reddy et al (2020a) showed an increase in primary root length under low P. Sarker and Karmoker (2009) showed the same result in lentils and observed that increased root meristem volume was associated with an increase in root length under P-deficient conditions.…”
Section: Discussionmentioning
confidence: 71%